SEQUENCE STRATIGRAPHY ANALYSIS OF TARAKAN FORMATION, RELATED WITH RESERVOIR DISTRIBUTION AND QUALITY IN TARAKAN SUB-BASIN, EAST KALIMANTAN - HADI WIJAYA, PRIATIN
Petroleum geological research in Tarakan Basin is relatively less than Kutai Basin such as detailed and comprehensively sequence stratigraphy, variation of sediment layering from transition to outer-neritic zone and its related to reservoir distribution and quality. Actually oil and gas exploration in Tarakan Basin, East Kalimantan, has been carried out since almost a hundred years ago and its include as the oldest basin in Indonesia. Unfortunately, offshore exploration in eastern part of offshore Tarakan Island has not yet been discovered oil and gas field significantly. This fact is contrary with offshore and deep-water of Kutai Basin that has discovered significant oil and gas fields i.e. West Seno and Gendalo Fields. The problem of this research are how to determine parasequence set, system-tract type, sedimentation facies and modeling of Tarakan Formation in eastern part of onshore and offshore Tarakan Island and then related with the reservoir rock distribution and quality. To solve the problem, I started from reference studies such as regional geology framework, tectonostratigraphy, petroleum system of Tarakan Sub-Basin and concept as well as basic understanding of sequence stratigraphy and reservoir aspects. Based on data available i.e. 2D seismic in SEGY-files, well log in LAS-file, biostratigraphy data summary and check-shot data, steps of research are sequence analysis and wells correlation, interpretation and analysis of seismic stratigraphy, subsurface mapping, reservoir distribution and quality analysis and finally 3D properties modeling for Vsh and effective porosity of net-reservoirs. This research methodology is to use several integrative softwares such as Microsoft Excell, Surfer, LogPlot and Petrel Schlumberger. The result of this research is Tarakan Formation can be divided into two sequences; T1 and T2 sequences. Both sequence has completely system-tract i.e. Lowstand System Tract (LST), Transgressive System Tract (TST) and Highstand System Tract (HST). The sequences include as type-1 sequence that lower sequence boundary is an erosion base due to forced regression. Each of sequence has variety of sedimentation, switching direction complex and intensively changing of geometry and position of sedimentation environmental unit. T2 sequence, younger than T1, has more expansive distribution and higher quality of reservoir than T1 sequence. Based on system-tract analysis, HST package of T2 sequence in the same location is generally better than LST dan TST package. There is a relationsip between sequence stratigraphy analysis and reservoir distribution and quality, especially in western and centre part of research location. T2 sequence that has higher reservoir quality is due to regressive phase increasingly dominant. Based on result of 3D properties modeling, rate of reservoir distribution and quality is to be had influence over basinward changing of lower intertidal borders and sand bar deposits of intertidal area.